2022
DOI: 10.21203/rs.3.rs-2183670/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Case Numbers as a Function of Regional Testing Strategy, Vaccination Coverage, and Vaccine Type

Abstract: Introduction The COVID-19 pandemic that began in 2019 has become a serious challenge for humanity almost everywhere globally. Despite active vaccination around the world, prevalence in different countries varies significantly as of May 2022. The reason may be a combination of demographic, immunological, and epidemiological factors. The purpose of this study was to analyze the relationship between COVID-19 prevalence in the population and the types of SARS-CoV-2 vaccines used in different countries globally, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The conducted cross-sectional, randomized study showed that by mid-April 2022, the total SARS-CoV-2 seroprevalence in the Armenian population included in the study reached 98.4% (95% CI 98.1-98.7). This significantly exceeds the previously postulated threshold beyond which epidemic spread of a pathogenic virus stops [18,22]. As expected, statistics provided by global sources show that after 15/04/2022, COVID-19 incidence in the RA decreased to almost zero, manifesting only in the form of individual sporadic cases in the subsequent period [3,6,12,17].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The conducted cross-sectional, randomized study showed that by mid-April 2022, the total SARS-CoV-2 seroprevalence in the Armenian population included in the study reached 98.4% (95% CI 98.1-98.7). This significantly exceeds the previously postulated threshold beyond which epidemic spread of a pathogenic virus stops [18,22]. As expected, statistics provided by global sources show that after 15/04/2022, COVID-19 incidence in the RA decreased to almost zero, manifesting only in the form of individual sporadic cases in the subsequent period [3,6,12,17].…”
Section: Discussionmentioning
confidence: 72%
“…It should also be noted that the vaccines used generated the same proportions of RBD seropositive. The reason for the noted features seems to be that inactivated vaccines contain the maximum set of viral antigens by design, unlike vector or especially mRNA preparations [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account the previously noted effectiveness of vector vaccines [40], the widespread use of the Sputnik family of vaccines may have become a significant factor behind decreasing COVID-19 incidence in the population. Another pattern confirming such a process is the inverse relationship between population humoral immunity and morbidity: an increase in post-vaccination resistance is inevitably accompanied by a decrease in morbidity [23,[41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%